2019
DOI: 10.1387/ijdb.180324mc
|View full text |Cite
|
Sign up to set email alerts
|

Somatic cell nuclear transfer: failures, successes and the challenges ahead

Abstract: Somatic cell nuclear transfer (SCNT) has a broad spectrum of potential applications, including rescue of endangered species, production of transgenic animals, drug production, and regenerative medicine. Unfortunately, the efficiency of SCNT is still disappointingly low. Many factors affecting cloning procedures have been described in several previous reviews; here we review the most effective improvements in SCNT, with a special emphasis on the effect of mitochondrial defects on SCNT embryo/ foetus development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 76 publications
1
32
0
Order By: Relevance
“…In turn, an overabundance of the somatic cell-derived agents modulating the epigenetic profile of the donor nucleus may remarkably reduce the concentration and activity of the oocyte's epigenetic factors. Thus, it may diminish the incidence of complete epigenetic reprogramming of transcriptional activity of the somatic cell nucleus in the developing cloned embryo [112,[132][133][134][135][136][137][138][139][140][141].…”
Section: Direct Intraooplasmic Microinjection Of Karyoplastsmentioning
confidence: 99%
“…In turn, an overabundance of the somatic cell-derived agents modulating the epigenetic profile of the donor nucleus may remarkably reduce the concentration and activity of the oocyte's epigenetic factors. Thus, it may diminish the incidence of complete epigenetic reprogramming of transcriptional activity of the somatic cell nucleus in the developing cloned embryo [112,[132][133][134][135][136][137][138][139][140][141].…”
Section: Direct Intraooplasmic Microinjection Of Karyoplastsmentioning
confidence: 99%
“…Although SCNT has been successfully used to clone many species of mammals with significant improvements in cloning efficiency in more than 20 years since the birth of Dolly, the proportion of cloned embryos that develop to full term remains very low, greatly limiting the application of SCNT technology (Czernik et al, 2019). To improve the birth of cloned mammals and cloning efficiency, researchers have investigated the effects of donor cell type, oocyte maturation stage, embryo activation method, etc.…”
Section: Low Cloning Efficiency Limits the Applicability Of Scntmentioning
confidence: 99%
“…Attempts are made to overcome these problems to develop and improve the maturation medium from the maturity of the oocytes to the development of embryos in the laboratory by adding supplementation to the ova maturation medium, then fertilization and embryo development ( Mishra et al, 2016 ). Recent reporting of the Red List by International Union for Conservation of Nature (IUCN) has highlighted that twenty-one percent of all mammals are at jeopardy of being extinct globally ( Czernik et al, 2019 , FAO, 2018 ). Various studies have highlighted a scientific conviction that this would allow the cell expansion and reestablishment using the popular and unique somatic cell nuclear transfer (SCNT) technology ( Hildebrandt et al, 2018 , Saragusty et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that TSA does induce hyperacetylation of histones and suppresses remethylation of DNA, leading to the un-methylated status of injected nuclei in oocytes ( Mishra et al, 2016 ). Further, this TSA cloning technique led to the first success in cloning the adult Institute of Cancer Research (ICR) mouse, an outbred strain that was directly cloned for the first time in history ( Czernik et al, 2019 ). Beside mouse, some studies showed that TSA treatment resulted in higher pre-implantation embryonic development in pigs ( Wang et al, 2018 ), cattle ( Ding et al, 2008 ), and rabbits ( Zeng et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%